تطوير نموذج لمتحكم عائم لتقدير نسبة التشغيل لمبدل خافض الجهد المستمر لتحسين كفاءة نظم الطاقة الشمسية الكهروضوئية عند التغيرات الجوية باستخدام Matlab/Simulink - ديلانة إيمان (Latakia University Journal -Engineering Sciences Series, 2018)
The research presents a new model for Fuzzy Logic Controller to track the Maximum Power Point for Solar Photovoltaic Energy, in order to obtain the maximum power of these systems under atmospheric changes. The model for Fuzzy Logic Controller developed in Matlab/Simulink environment, depends on the use of instantaneous measurements of the solar cell temperature and solar radiation intensity, to determine the optimal duty cycle used to control the duty cycle of Buck converter to achieve the Photovoltaic system works at the maximum power point. Thus, the proposed controller in the research considered, independent in his work on the use of electrical measurements output of PV system to determine optimal duty cycle. This would improve the dynamic performance of the proposed Fuzzy Logic Controller to determine the duty cycle at fast speed proportional to the changes speed of different weather condition. We selected Generalized bell curve membership functions for fuzzification the input variables of DMPPT-FLC Controller to suit the nature of the nonlinear changes to these variables, and Triangular membership functions and other Trapezoidal membership function for the fuzzification of the output variable. The simulation results completed in Matlab /Simulink environment, showed the best performance of the proposed Fuzzy Logic Controller, in tracking the MPP point at fast speed and high accuracy, which improves the value of efficiency factor of the PV system, compared with the use of other reference models of fuzzy logic controller MPPT-FLC functioning relies on the use of a number of electrical measurements of the output of PV system, and compared with the use of the conventional Perturb and Observer technique MPPT- P&O under different atmospheric changes. يقدم البحث نموذج جديد لمتحكم عائم لتتبع نقطة الاستطاعة العظمى لنظم الطاقة الشمسية الكهروضوئية PV، بهدف الحصول على الطاقة القصوى من هذه النظم في ظل التغيرات الجوية. يعتمد نموذج المتحكم العائم المطور في بيئةMatlab/Simulink ، على استخدام القياسات اللحظية لدرجة حرارة الخلية الشمسية وشدة الإشعاع الشمسي، لتحديد نسبة التشغيل المثلى المستخدمة للتحكم في دورة عمل مبدل خافض الجهد المستمر لتحقيق عمل النظام الكهروضوئي عند نقطة الاستطاعة العظمى. بالتالي يعتبر المتحكم العائم DMPPT-FLC المقترح في البحث، مستقل في عمله عن استخدام القياسات الكهربائية لخرج نظام PV لتحديد نسبة التشغيل. هذا من شأنه تحسين الأداء الديناميكي للمتحكم العائم المقترح بتحديد نسبة التشغيل بسرعة فائقة متناسبة مع سرعة التغيرات الجوية المختلفة. تم اختيار توابع انتماء جرسية الشكل لتعويم متغيرات الدخل للمتحكم DMPPT-FLC لتلائم طبيعة التغيرات اللاخطية لهذه المتغيرات، وتوابع انتماء مثلثية وأخرى شبه منحرف لتعويم متغير الخرج. أظهرت نتائج المحاكاة المنجزة في بيئة Matlab/Simulink الأداء الأفضل للمتحكم العائم المقترح DMPPT-FLC، بتتبع نقطة MPP بسرعة فائقة وبدقة عالية مما يحسن بشكل ملحوظ من قيمة عامل كفاءة نظام PV، مقارنة مع استخدام نماذج مرجعية أخرى لمتحكم عائم MPPT-FLC يعتمد عملها على استخدام عدد من القياسات الكهربائية لخرج نظام PV، ومقارنة مع استخدام متحكم تقليدي MPPT-P&O يعتمد على تقنية الاضطراب والمراقبة عند التغيرات الجوية المختلفة.